Effects of a 12-Week Cycling Intervention on Successful Aging Measures in Mid-Aged Adults. Issue 1 (2nd January 2021) - Geard, David; Rebar, Amanda L.; Dionigi, Rylee A.; Rathbone, Evelyne; Reaburn, Peter
ABSTRACT: Purpose : To compare the effect of 12-weeks of cycling training and competition versus recreational cycling on successful aging across physical, psychological, cognitive, and social functioning domains in mid-aged adults. Methods : Recreational cyclists were randomly assigned to an intervention ( n = 13, M age = 47.18 years) and comparison ( n = 13, M age = 46.91 years) group. Analysis of Covariance was used on self-reported pre-post data to determine changes across time and differences between groups on outcomes. Results : The intervention group scored higher on the role limitation due to physical problems measure of physical functioning ( p = .045) and the social activity measure of social functioning ( p = .008) with large effect sizes ( ηp 2  > .14). The remaining physical, psychological, cognitive, and social functioning measures were not significantly different ( p > .05) between groups with small to medium effect sizes ( ηp 2  > .01 to ≤ .06). Conclusion : Cycling training and competition promotes better physical and social functioning than recreational cycling. This finding indicates that an intervention that incorporates the training and competition aspects of sport may promote positive outcomes that are above and beyond those that can be gained from participation in recreational physical activity. Objective measurements on larger samples across a broader range of sports are required to confirm and extend these findings.